IDENTIFIKASI SISA MATERIAL KONSTRUKSI PADA PROYEK PEMBANGUNAN PELABUHAN - Yusrizal, Muhamad; Setiawan, Budi (Civil Engineering Scientific Journal, 2023)
ABSTRACT: Construction project activity is a long process, in its implementation many problems and obstacles are encountered. One of them is the problem of residual material which is a serious problem in the implementation of construction projects. Efforts to minimize waste of construction materials will help increase profits and reduce environmental impact. Based on these problems, it is necessary to conduct research on materials that have the potential to become residual materials. Data collection was obtained from the company administration to support the calculation. Data processing begins with classifying material types, identifying potentially waste material with pareto analysis, calculating waste volume, calculating waste level, ranking potentially waste material based on waste level, calculating waste cost, ranking potentially waste material based on waste cost, structured interviews with respondents . From the results of material analysis, the remaining construction materials for the Port Development Project (Case Study: Development of Tengkayu Port 1 Phase 5, Tarakan City), are 5 mm dark blue glass, galvanized 5", 60x60 cm granite, ACP cover, 0.6 mm solar flat roof, aluminum sills 4", 10 mm plate, steel Ã˜ 4 " (114.3 mm) t = 4.5 mm, iron pipe 10 " (267.44 mm) t = 6.6 mm, iron D16, iron D12. The material that has the highest volume and cost is 5 mm dark blue glass with a total waste cost of Rp. 101,399,197.87.Keywords: Identification, Construction, MaterialABSTRAK: Kegiatan proyek konstruksi merupakan suatu proses yang panjang, dalam pelaksanaannya banyak dijumpai masalah dan kendala. Salah satunya permasalahan sisa material yang merupakan salah satu masalah serius pada pelaksanaan proyek konstruksi. Usaha meminimalkan sisa material konstruksi akan membantu meningatkan keuntungan dan mengurangi dampak lingkungan. Berdasarkan permasalahan tersebut perlu dilakukan penelitian terhadap material yang berpotensi menjadi sisa material. Pengumpulan data diperoleh dari pihak administrasi perusahaan untuk menunjang perhitungan. Pengolahan data diawali dengan menglompokkan jenis material, mengidentifikasi material yang berpotensi waste dengan analisa pareto, menghitung volume waste, menghitung waste level, merangking material yang berpotensi waste berdasarkan waste level, menghitung waste cost, merangking material berpotensi waste berdasarkan waste cost, wawancara terstruktur terhadap responden. Dari hasil analisa material yang menjadi sisa material konstruksi pada Proyek Pembangunan Pelabuhan (Studi Kasus: Pengembangan Pelabuhan Tengkayu 1 Tahap 5 Kota Tarakan), adalah kaca dark blue 5 mm, galvanize 5", granito 60x60 cm, cover ACP, atap solarflat 0.6 mm, kusen aluminium 4", plat 10 mm, besi Ã˜ 4 " (114.3 mm) t = 4.5 mm, besi pipa 10 " (267.44 mm) t = 6.6 mm, besi D16, besi D12. Dengan material yang memiliki volume dan biaya tertinggi adalah kaca dark blue 5 mm dengan total waste cost sebesar Rp. 101.399.197,87.Kata kunci: Identifikasi, Konstruksi, Material